2014
DOI: 10.1371/journal.pone.0088405
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NADPH Oxidase 5 by Protein Kinase C Isoforms

Abstract: NADPH oxidase5 (Nox5) is a novel Nox isoform which has recently been recognized as having important roles in the pathogenesis of coronary artery disease, acute myocardial infarction, fetal ventricular septal defect and cancer. The activity of Nox5 and production of reactive oxygen species is regulated by intracellular calcium levels and phosphorylation. However, the kinases that phosphorylate Nox5 remain poorly understood. Previous studies have shown that the phosphorylation of Nox5 is PKC dependent, but this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 79 publications
2
81
1
Order By: Relevance
“…Gelsolin protein levels increase when lung cancer cells receive differentiation stimuli (Jarrard et al, 1998), and we previously detected cancer (glioma) cell differentiation after membrane lipid remodeling as an intermediate step before programmed cell death (Terés et al, 2012). Fatty acids can induce ROS production through mitochondrial events (Schonfeld and Wojtczak, 2008) and by enhanced activity of the NAD(P)H-oxidase stimulated by PKC (Chen et al, 2014). ROS are known to produce apoptosis and to act as mediators in signal transduction pathways, such as the mitogen-activated protein kinase pathway (Cagnol and Chambard, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Gelsolin protein levels increase when lung cancer cells receive differentiation stimuli (Jarrard et al, 1998), and we previously detected cancer (glioma) cell differentiation after membrane lipid remodeling as an intermediate step before programmed cell death (Terés et al, 2012). Fatty acids can induce ROS production through mitochondrial events (Schonfeld and Wojtczak, 2008) and by enhanced activity of the NAD(P)H-oxidase stimulated by PKC (Chen et al, 2014). ROS are known to produce apoptosis and to act as mediators in signal transduction pathways, such as the mitogen-activated protein kinase pathway (Cagnol and Chambard, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…A previous study demonstrated that PKC inhibitor Ro318220 specifically inhibited PMA-stimulated DUOX2 phosphorylation and H 2 O 2 production in COS-7 cells, suggesting PKC is a critical regulator of DUOX2 phosphorylation [28]. Moreover, it also has been reported that PKCa can phosphorylate NOX5 and enhance its activity [29]. Therefore, it is possible that PKCa may promote DUOX2 expression and activity by stimulating its phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The level of nitrite (NO2)/nitrate (NO 3) concentrations in the conditioned medium was measured using a nitric oxide detection kit (ENZO Life Sciences) according to the manufacturer's instructions. In brief, following filtration in a 10-kDa spin column (Biovision) 50 l of the culture medium were diluted with 50 l of reaction buffer containing 50 M L-N 6 -(1-iminoethyl)lysine hydrochloride [L-NIL, a selective inducible NOS (iNOS) inhibitor] and mixed with 25 l NADH and 25 l nitrate reductase.…”
Section: Methodsmentioning
confidence: 99%